Discovery of Novel Inhibitors of Aspergillus fumigatus DHODH via Virtual Screening, MD Simulation, and In Vitro Activity Assay - Kaige Li; Wei Xia; John Z. H. Zhang (Molecules, 2025)
To address the surge in Aspergillus fumigatus infections among immunosuppressed patients and azole resistance, this study focused on developing novel inhibitors targeting dihydroorotate dehydrogenase (AfDHODH), a key enzyme in fungal pyrimidine synthesis. The three-dimensional structure of AfDHODH was constructed via homology modeling. Molecular docking, dynamics simulations, and binding free energy calculations systematically elucidated the mechanisms of existing inhibitors. Virtual screening against the ZINC20 and ChEMBL databases yielded 13 candidates, with two micromolar inhibitors (IC50 < 100 μM) identified through in vitro assays. These inhibitors exhibited novel scaffold structures that were distinct from known DHODH inhibitors. The results validate the feasibility of homology modeling-guided antifungal discovery and these findings provide critical insights for the development of new antifungal agents.